CLINICAL EXPERIENCE OF MICROSURGICAL REMOVAL OF INTRAVENTRICULAR EPIDERMOID TUMOR (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Intraventricular epidermoid tumors (cholesteatomas) are relatively rare, slow-growing neoplasms that are usually associated with hydrocephalus. They form due to the failure of epidermal remnants to regress during embryogenesis. Epidermoid cysts have a lipid-like consistency and are most commonly localized in the brain's ventricles and basal structures. As these tumors grow, they can obstruct the ventricular system, leading to increased intracranial pressure and obstructive hydrocephalus viruses, bacteria